2020
DOI: 10.4236/ojee.2020.91003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Energy Losses in a Barbecue Oven in Burkina Faso

Abstract: This work concerns an experimental and numerical study of energy losses in a typical oven usually used in the agro-food craft sector in Burkina Faso. The experimental results were obtained by infrared thermography of the oven and by monitoring the evolution of the wall temperatures using thermocouples connected to a data acquisition system. These results indicate that the energy losses are mainly through the walls of the oven. The numerical study based on the energy balance and corroborated by the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our previous work, we have shown that grilling equipment lost almost half of the fuel consumed mainly through the walls [20]. We have also shown that the energy efficiency of fired-wood ovens used in Burkina Faso is low (around 19%) [21].…”
Section: Introductionmentioning
confidence: 94%
“…In our previous work, we have shown that grilling equipment lost almost half of the fuel consumed mainly through the walls [20]. We have also shown that the energy efficiency of fired-wood ovens used in Burkina Faso is low (around 19%) [21].…”
Section: Introductionmentioning
confidence: 94%
“…Meat rotisserie in Burkina Faso is a lucrative activity which provides substantial revenues to the actors. Unfortunately, most equipment has very low efficiency and we have highlighted this problem through a study carried out on grilling equipment [1]. This low efficiency represents a net loss of income for the players who spend more than necessary on fuel.…”
mentioning
confidence: 99%